Exploring the Grit Narrative through Andragogy: Implications for Adult Education - Jennifer L Pemberton; Ted McCadden (Adult Education Research Conference, 2019)
An exploration of the intersection of andragogy and the grit narrative serves to position grit in the adult education literature and considers the unsuitability of this ideology for adult learners.
Keywords: andragogy; grit; self-directed learning